(untitled) (Advances in Applied Mathematics and Mechanics, 2013)
In this paper, the Crank-Nicolson linear finite volume element method is applied to solve the distributed optimal control problems governed by a parabolic equation. The optimal convergent order O(h^2+k^2) is obtained for the numerical solution in a discrete L^2-norm. A numerical experiment is presented to test the theoretical result.